Application of certain homoeopathic medicines used against fruit rot of apple caused by Penicillium expansum Link - Baviskar RN; Suryawanshi NS (International Journal of Life Sciences, 2015)
Blue mold of apple caused by Penicillium expansum is one of the most important serious destructive post harvest disease in India. Twenty three isolates of Penicillium expansum were isolated from rotted fruits of apple collected from APMC fruit market of Vashi, Navi Mumbai. Their sensitivity was tested against carbendazim. It was found that Pe-9 was sensitive while pe-15 resistant. MIC values ranged from 750.6-970.3μg/ml. Sensitive isolate was selected for further studies and treated with chemical and physical mutagens and resistant mutant of P.expansum (Pe-EMS-10) was found (4850.6g/ml). Of 13 homoeopathic medicines were used for the management of carbendazim resistant mutant of Penicillium expansum (EMS-Pe-10). Sepia officinale was more effective PCE value (40.42) when used individually and in mixture with carbendazim PCE value was increased as compared to individual (53.25) and followed by Arsenicum album, Tabacum, Cynopodium, Baptisia tinctoria, Ustilago maydis, Iris versicolor, Zincum metallicum and Argentum metallicum.